Downregulation of Orco and 5-HTT Alters Nestmate Discrimination in the Subterranean Termite Odontotermes formosanus (Shiraki) - Sun, Pengdong; Yu, Shuxin; Merchant, Austin; Lei, Chaoliang; Zhou, Xuguo; Huang, Qiuying (Frontiers in Physiology, 2019)
Nestmate discrimination allows social insects to recognize nestmates from non-nestmates using colony-specific chemosensory cues, which typically evoke aggressive behavior toward non-nestmates. Functional analysis of genes associated with nestmate discrimination has been primarily focused on inter-colonial discrimination in Hymenopterans, and parallel studies in termites, however, are grossly lacking. To fill this gap, we investigated the role of two genes, Orco and 5-HTT, associated with chemosensation and neurotransmission respectively, in nestmate discrimination in a highly eusocial subterranean termite, Odontotermes formosanus (Shiraki). We hypothesized that knocking down of these genes will compromise the nestmate recognition and lead to the antagonistic behavior. To test this hypothesis, we carried out 1) an in vivo RNAi to suppress the expression of Orco and 5-HTT, respectively, 2) a validation study to examine the knockdown efficiency, and finally, 3) a behavioral assay to document the phenotypic impacts/behavioral consequences. As expected, the suppression of either of these two genes elevated stress level (e.g., vibrations and retreats), and led to aggressive behaviors (e.g., biting) in O. formosanus workers towards their nestmates, suggesting both Orco and 5-HTT can modulate nestmate discrimination in termites. This research links chemosensation and neurotransmission with nestmate discrimination at the genetic basis, and lays the foundation for functional analyses of nestmate discrimination in termites.